2010
DOI: 10.1118/1.3352586
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical background and generalized detectability in tomosynthesis and cone‐beam CT

Abstract: The complex tradeoffs among anatomical background, quantum noise, and electronic noise in projection imaging, tomosynthesis, and CBCT can be described by generalized cascaded systems analysis, providing a useful framework for system design and optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
147
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 49 publications
5
147
0
Order By: Relevance
“…3 decades (78,79). These model observers have been applied to many different imaging modalities to narrow the range of acceptable imaging conditions and to improve the efficiency of system optimization (80), including nuclear medicine imaging (81)(82)(83), mammography (84-87), dual-energy radiography (88), tomosynthesis and flat-panel cone-beam CT (89)(90)(91), and magnetic resonance imaging (92). However, relatively few studies have been performed with clinical CT (93,94).…”
Section: Acknowledgmentmentioning
confidence: 99%
“…3 decades (78,79). These model observers have been applied to many different imaging modalities to narrow the range of acceptable imaging conditions and to improve the efficiency of system optimization (80), including nuclear medicine imaging (81)(82)(83), mammography (84-87), dual-energy radiography (88), tomosynthesis and flat-panel cone-beam CT (89)(90)(91), and magnetic resonance imaging (92). However, relatively few studies have been performed with clinical CT (93,94).…”
Section: Acknowledgmentmentioning
confidence: 99%
“…The approach provides a general framework that has been applied fairly broadly for modeling and optimization of 2D imaging systems, [15][16][17][18] as well as 3D modalities such as CBCT. 14,[19][20][21] The complete model of a CBCT imaging system 20,22 consists of 13 stages, including: a 2D projection cascade describing the physical processes from interaction of x-rays in the converter to sampling and readout of the detector with additive noise (and optional pixel binning 22 ); and a 3D cascade describing the mathematical processes of filtered backprojection, from log-transform of the projection data to discrete sampling of the 3D reconstruction matrix. 22 The studies reported below were limited to an investigation of the resolution (presampling detector MTF) and DQE inherent to the 2D image acquisition component of the proposed system via the 2D projection model.…”
Section: Iic1 Cascaded Systems Modelmentioning
confidence: 99%
“…Specifically, optimization of the x-ray source scan angle and angular sampling scheme is an area of interest in recent literature. [6][7][8][9][10][11][12][13][14][15][16][17] These studies could reduce the number of physical prototype iterations and eventually lead to task-and patient-specific optimization of tomosynthesis. But to achieve these goals, we first need accurate, task-based strategies for evaluating key DBT system parameters in simulation.…”
Section: Introductionmentioning
confidence: 99%